Between Measure and Excess: The Roman Republic in Louisa May Alcott’s Moods - Vellucci, Sabrina (Oltreoceano - Rivista sulle migrazioni, 2021)
Louisa May Alcott’s Moods and the sensation tales the author published in the 1860s exceeded narrative, racial, and gender boundaries. References to the Roman Republic came to epitomize the sentimental excess that was beginning to be censored by the literary establishment. Tra eccesso e misura: la Repubblica Romana in Moods di Louisa May Alcott Il romanzo Moods e i racconti a sensazione che Louisa May Alcott pubblicò nel decennio 1860 trasgredivano i confini narrativi, razziali e di genere. I riferimenti alla Repubblica Romana finirono col simboleggiare gli eccessi sentimentalisti censurati dall’establishment letterario.